2021
DOI: 10.3390/ijms222413551
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Contributions of NMDA Receptors and L-Type Calcium Channels to Long-Term Depression in the Piriform Cortex

Abstract: In the hippocampus, the contributions of N-methyl-D-aspartate receptors (NMDARs) and L-type calcium channels (LTCCs) to neuronal transmission and synaptic plasticity change with aging, underlying calcium dysregulation and cognitive dysfunction. However, the relative contributions of NMDARs and LTCCs in other learning encoding structures during aging are not known. The piriform cortex (PC) plays a significant role in odor associative memories, and like the hippocampus, exhibits forms of long-term synaptic plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Recently, we demonstrated that similar to the hippocampus, there is an age-dependent increase in the contribution of LTCCs to LTD in the PC, concurrent with a decreased role for NMDARs (Rajani et al, 2021). Moreover, inhibition of LTCCs in the aging piriform cortex blocks LTD (Rajani et al, 2021) and could enhance learning (Maziar et al, 2022). The increased significance of LTCCs during aging may provide some insight into the susceptibility of the aged PC to AD-related changes of the LC-NE pathway (Figure 3).…”
Section: Norepinephrine Modulation Of Calcium Channels In Alzheimer's...mentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, we demonstrated that similar to the hippocampus, there is an age-dependent increase in the contribution of LTCCs to LTD in the PC, concurrent with a decreased role for NMDARs (Rajani et al, 2021). Moreover, inhibition of LTCCs in the aging piriform cortex blocks LTD (Rajani et al, 2021) and could enhance learning (Maziar et al, 2022). The increased significance of LTCCs during aging may provide some insight into the susceptibility of the aged PC to AD-related changes of the LC-NE pathway (Figure 3).…”
Section: Norepinephrine Modulation Of Calcium Channels In Alzheimer's...mentioning
confidence: 97%
“…LTCCs are downstream of β-adrenergic receptors, via a G s -mediated cAMP-PKA pathway to produce an increase in Ca 2+ influx and CREB-mediated protein synthesis and the initiation of long-term memory formation (Ghosh et al, 2017a;Man et al, 2020). Recently, we demonstrated that similar to the hippocampus, there is an age-dependent increase in the contribution of LTCCs to LTD in the PC, concurrent with a decreased role for NMDARs (Rajani et al, 2021). Moreover, inhibition of LTCCs in the aging piriform cortex blocks LTD (Rajani et al, 2021) and could enhance learning (Maziar et al, 2022).…”
Section: Norepinephrine Modulation Of Calcium Channels In Alzheimer's...mentioning
confidence: 98%
See 1 more Smart Citation
“…This age-related modification of the expression and function of LTCCs in hippocampal neurons could contribute to dysregulated calcium homeostasis, resulting in synaptic dysfunction and cognitive decline [115] , although a protective role of increased LTCC plasticity in aging has also been proposed [19] , [92] . Recently, we demonstrated that similarly to the hippocampus [19] , [92] , [134] , there is an age-dependent increase in the contribution of LTCCs to LTD in the piriform cortex (PC), concurrent with a decreased role for NMDARs [129] . Moreover, inhibition of LTCCs in the aged PC blocks LTD [129] and could consequently enhance learning [107] .…”
Section: Ltcc In Synaptic Plasticity and Learning: Effects Of Aging A...mentioning
confidence: 99%
“…Recently, we demonstrated that similarly to the hippocampus [19] , [92] , [134] , there is an age-dependent increase in the contribution of LTCCs to LTD in the piriform cortex (PC), concurrent with a decreased role for NMDARs [129] . Moreover, inhibition of LTCCs in the aged PC blocks LTD [129] and could consequently enhance learning [107] . LTCC dysregulation is suggested in models for age-related cognitive decline [157] and is likely involved in AD.…”
Section: Ltcc In Synaptic Plasticity and Learning: Effects Of Aging A...mentioning
confidence: 99%